Evaluation of Effective Interfacial Area in a Rotating Packed Bed Equipped with Dual Gas Inlets - Usman Garba; David Rouzineau; Michel Meyer (ABUAD Journal of Engineering Research and Development)
This study investigates the effective interfacial area in a novel rotating packed bed (RPB) equipped with dual gas inlets instead of the conventional single-gas-inlet RPB. The aim is to enhance the mass transfer efficiency of gas-liquid contacting processes in RPBs by increasing the number of gas inlets to improve the spread of gas supply into the packing. The RPB is a promising gas-liquid contactor configuration known for its intensified mass transfer characteristics. However, the impact of additional gas inlets on the effective interfacial area of the packing remains unexplored. An experimental method assessed the interfacial area under varying operational conditions which include a liquid flow rate of 0.30-0.60 m3/h, a gas flow rate of 100-300 Nm3/h, and a rotation speed of 600-1000 rpm. At operating conditions covering the maximum rotation speed of 1400 rpm, gas flow and liquid flow rates of 300 Nm3/h and 0.60 m3/h respectively, the results showed that on average, 55 to 97% of the 2400m2/m3 specific packing area can be effectively utilized for gas-liquid mass transfer during separation operations using the RPB. Compared to results reported for single-gas-inlet RPBs using similar packings, the RPB with double gas inlet proved to provide higher utilization of the packing. By simply doubling the number of gas inlets, the findings provide valuable insights into optimizing RPB designs and operations which could enhance mass transfer efficiency for various chemical and environmental applications.